PUI: Organisasi dan Perkembangannya Sejak Berdiri Hingga Pemilu 2009 - Emil Permanasari (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2019)
Islamic Community Unity develops in the form of conflict or disintegration, such as: how they choose to leave the members of the Masyumi major party or postpone the implementation of the 4th and 5th Islamic Society Unity Congress (PUI) efforts to explain what is needed. The development of Islamic Unity until the reform era was still in a "silent" position as a dying organization. It was only in the 1999, 2004 and 2009 elections that a number of cadres and congregations of Islamic Unity began to become members of political parties and without hesitation called themselves pilgrims or cadres of Islamic Unity. Islamic Unity chooses the path of conflict resolution by compromise, namely the goal of integration. The paper is a literature study that explains PUI's organization based on its concept and development. The PUI mass organization is a combination of two mass Islamic organizations that grew and were established by West Javanese. The two organizations are Muslim Engagement centered in Majalengka with founding figures Abdoel Halim and Indonesian Islamic Community Association based in Sukabumi with founding figure Ahmad Sanoesi. The process of birth and development of Islamic Unity from 1911-2011 as a mass Islamic organization is a complex matter. Organizationally Islamic Unity is declared an "Independent" organization and is not affiliated with any of the organizations. Focusing on social, educational and religious movements. PUI is a Muslim Community Unity Movement which was formed with the aim and effort to achieve the realization of the Great Islam and happiness of the people.Keywords: Islamic Community Unity, PUI concept, Islamic organizationAbstrakPersatuan Umat Islam berkembang dalam bentuk konflik atau disintegrasi, seperti: bagaimana mereka memilih keluar dari anggota partai besar Masyumi atau melakukan pengunduran pelaksanaan Muktamar Persatuan Umat Islam (PUI) ke-4 dan ke-5 upaya untuk menjelaskan hal-hal yang diperlukan. Perkembangan Persatuan Umat Islam hingga era reformasi masih dalam posisi “diam” sebagai organisasi sekarat. Baru pada Pemilu 1999, 2004, dan Pemilu 2009, sejumlah kader dan jama'ah Persatuan Umat Islam mulai menjadi anggota partai politik dan dengan tanpa ragu menyebut diri sebagai jama'ah atau kader Persatuan Umat Islam. Persatuan Umat Islam memilih jalan penyelesaian konflik dengan cara kompromi, yaitu tujuan yang terwujudnya integrasi. Adapun Karya tulis ini merupakan studi literatur yang menjelaskan organisasi PUI berdasarkan konsep dan perkembangannya. Organisasi massa PUI merupakan gabungan dari dua organisasi massa Islam yang tumbuh dan didirikan oleh orang Jawa Barat. Kedua organisasi itu adalah Perikatan Umat Islam berpusat di Majalengka dengan tokoh pendiri Abdoel Halim dan Persatuan Umat Islam Indonesia berpusat di Sukabumi dengan tokoh pendiri Ahmad Sanoesi. Proses kelahiran dan perkembangan Persatuan Umat Islam dari 1911-2011 sebagai organisasi massa Islam merupakan hal yang kompleks. Secara organisatoris Persatuan Umat Islam dinyatakan sebagai organisasi yang “Independen” dan tidak berafiliasi pada salah satu organisasi manapun. Menitikberatkan pada gerakan sosial, pendidikan dan keagamaan. PUI Merupakan Gerakan Persatuan Umat Islam yang dibentuk dengan tujuan dan usaha mencapai terwujudnya Islam Raya dan kebahagian umat. Kata kunci: Persatuan Umat Islam, konsep PUI, organisasi Islam